Three Stories of the Journey To Canada - Jama, Sagal (Contingent Horizons: The York University Student Journal of Anthropology, 2022)
In 1990 a civil war began in Somalia that would change the state of the country for decades. With the war came the countless people who fled from the conflict for a safer life. Since the 90s the rise of Islamic Terrorism has made the conflict even more complicated, further creating more refugees in the 2000s and today. In the Somali diaspora, there are a number of communities in many countries including in Toronto, Canada. As the world has more refugees today than in modern history, understanding the journey they take both physically and mentally is important as it is a traumatic and often grueling experience. Using the many tools from anthropology this article seeks to understand three women who took such a journey to Canada and how it plays into larger themes in the Somali Diaspora.